1992
DOI: 10.1136/bmj.305.6866.1399
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of missed abortion and anembryonic pregnancy.

Abstract: Symptoms of bronchial hyperreactivity and asthma in relation to environmental factors. Arch Dis Child 1988;63:473-8. 18 Lunn JE, Knowelden J, Roe JW. Pattems of respiratory illness in Sheffield junior schoolchildren-a follow up study. BrJ Prev Soc Med 1970;24:223-8. 19 Ware JH, Ferris BG Jr, Dockerv DW, Spengler JD, Stram DO, Speizer FE.Effects of ambient sulfur oxides and suspended particles on respiratory health of pre-adolescent children. Am Rev Respir Dis 1986;133:834-42. 20 Braun-Fahrlander C, Ack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
1
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 2 publications
1
47
1
4
Order By: Relevance
“…This success rate is within the range of 52%-95% reported in earlier studies (3,18,(21)(22)(23)(24). Of these studies, all but one (24) enrolled only patients with missed abortion.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This success rate is within the range of 52%-95% reported in earlier studies (3,18,(21)(22)(23)(24). Of these studies, all but one (24) enrolled only patients with missed abortion.…”
Section: Discussionsupporting
confidence: 58%
“…Protocols combining mifepristone and PG analogs for the treatment of early pregnancy failure have been studied, showing a success rate ranging from 52% to 84% (3,18,(21)(22)(23)(24). However, to date the only randomized study reported found no improvement in the success rate of misoprostol for termination of early pregnancy failure after mifepristone pretreatment (18).…”
mentioning
confidence: 97%
“…9,10 Misoprostol used alone for nonviable first-trimester pregnancy resulted in uterine expulsion in 13% to 96% of women. 11,12 Explanations for this wide range include different indications for treatment, dosing regimen, routes of administration, and measures of success. Vaginal administration appears to be more effective than oral administration for the inducement of uterine contractions and cervical effacement, 10 while minimizing systemic side effects (such as diarrhea, fever, nausea, and vomiting).…”
mentioning
confidence: 99%
“…9,10 Misoprostol used alone for nonviable first-trimester pregnancy resulted in uterine expulsion in 13% to 96% of women. 11,12 Explanations for this wide range include different indications for treatment, dosing regimen, routes of administration, and measures of success.…”
mentioning
confidence: 99%
“…Plasma concentrations and bioavailability of PGE1 tend to be higher when administered vaginally rather than orally, Zieman et al 5 Vaginal administration of PGE1 has been shown to be more effective in comparison with oral route in context of medication abortion, Crenin et al 6 Although incomplete miscarriage may be managed with PGE1 alone, in the presence of early fetal demise, priming with antiprogesterone Mifepristone makes the regime more effective, El Rafaey et al, Hinshaw 1997. 7,8 WHO task force in 1993 has suggested that for termination of early pregnancy, a single dose of 200mg of mifepristone is as effective as 600mg, when used in combination with PGE1. 9 Most studies using PGE1 alone for medical management of delayed miscarriage have a success rate of 13-83%, de Jonge et al 10 Overall complete abortion was 97.6% in a study by PW Ashok et al 11 Chung et al, reported an overall efficacy rate of 70.6%.…”
Section: Discussionmentioning
confidence: 99%